(untitled) (Research, Society and Development, 2022)
COVID-19 is a disease caused by the SARS-CoV-2 virus discovered in Wuhan city, China, in November 2019. In view of the rapid transmissibility, the unknown virulence and the course of the disease, in March 2020, the WHO considered Covid a global emergency pandemic. That same month, pregnant women were classified as risk groups, having priority in intensive care and vaccination. Pregnant women in view of their physiology are at greater risk of not only becoming infected, but of developing the most severe forms of the disease. In this context, the present article had as main objective to perform an integrative literature review addressing the main clinical manifestations of the severe and critical form of COVID-19 in pregnant women. The search was conducted from the databases PUBMED and BVSalud during the months of August and September 2022. Initially, 888 articles were found that after the exclusion of duplicates and the selection through the inclusion and exclusion criteria resulted in 474 articles for the full reading. According to the review, the most frequent complications are respiratory, cardiovascular, neurological, and obstetric. Comorbidities, gestation time and the need for intensive care were significantly associated with negative outcomes in pregnant women.